Meningkatkan Kreativitas Siswa pada Nilai-Nilai Demokrasi dan Hak Azasi Manusia - Lumbangaol, Rumondang (JUPIIS: Jurnal Pendidikan Ilmu-ilmu Sosial, 2015)
The subject of this research is 24 students at class Natural Science-3 grade XII, while the subject is Teaching method of Tasking, as data collected by using observation list and questionaire. Based on pre test to 24 students, resulting 10 students obtained lower score and 11 students reached middle score, and only 3 students achieved good score with average score of 62.83 percent. Then in the first cycle of treatment, resulting 6 student were predicated good score, 12 students were predicated middle score, and the rest 6 students were predicated lower score with average score of 75.95 percent. In the second cycle of treatment, it climbs to 22 students reached good score, while 2 students obtained lower score, with average score of 86.16 percent. By the last questionaire, resulting 2 students got lower score, while 2 students got middle score and 20 students achieved good score, with average score of 88.08 percent. Based on the result of all first and second cycle, empirically proved that teaching method of tasking resulted increasing score significantly. Therefore, using teaching method of tasking could be elevate studentsâ creativity in the subject of Christian Religion at class Natural Science-3 grade XII in SMA 12 of Medan.